Perbedaan perilaku keluarga berencana pada masyarakat Oebelo dan Bismarak Kecamatan Kupang Tengah (The Difference of Family Planning Behavior on Oebelo and Bismarak Society, Subdistrict of Central Kupang) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Practically, the target of the number family planning acceptors in every region could not be same, when it is looked upon from either its number of acceptors or its quality due to the fact that the use of contraceptives is not very easily accepted by community, particularly by women. The study tries to reveal this particular problem, i.e., to examine the difference ofthe striking behaviour offamilty planning of the community of the Villages of Oebelo and Bismarak. It also investigates the demographic and socio-cultural factors which have the greatest influence on the difference of family planning behaviour of the community of these two villages. The areas chosen for the study were the Villages of Oebelo and Bismarak, two villages which have respectively, the lowest and the highest achievement of family planning in the Subdistrict of Central Kupang, Kupang Regency, NTT. The selection for the study areas was done through purposive sampling, whereas the respondents were ELCO women (women of eligible couples) aged between 15 to 44 years, having at least one living child, and who either had been or had not been family planning acceptors. The number of respondents of the two villages were 100 respectively. The data analysis was done by using cross tabulation with the Chi-Square technique and the contingency coefficient test. The result of the analysis showed that the level of education, the avaibility of family planning service, its perception on the value of children, the support of husband to female acceptors, on the perception on the attitude of the local authorities in supporting the family planning program, were factors which influence significantly on the low participation of family planning program, of the Village of Oebelo. The number of living children and the household income had little influence on the FP participation. In the Village of Bismarak, however, education and supply on family planning services had significant influence on the participation of the program.